Dose escalation or swap for loss of response to biological therapy in IBD? - JM Benítez Cantero (Revista Andaluza de Patología Digestiva, 2026)
Abstract Biological therapies have transformed the management of inflammatory bowel disease (IBD). Nevertheless, a substantial proportion of patients experience primary non-response or secondary loss of response during treatment. This phenomenon represents a major therapeutic challenge and often requires treatment optimization strategies. Among these, dose escalation increasing dosage or interval shortening, and switching to a drug with a different mechanism of action (swap) are the most frequently considered approaches. The decision between these strategies depends on several factors, including the type of therapeutic failure, drug serum concentrations, anti-drug antibodies and the patient’s clinical context. Therapeutic drug monitoring has emerged as a key tool to identify mechanisms of treatment failure and guide clinical decision-making. This article reviews the magnitude of loss of response to biological therapies in IBD, especially to anti-TNF agents, describes the underlying mechanisms and summarizes the available evidence to guide the choice between dose escalation and switching therapeutic targets.